Bringing Nature Closer: A Systematic Review of Virtual Reality’s Impact on Students’ Environmental Attitudes and Behavior - Alwan Faiz Fatihul (Journal of Innovative and Creativity, 2025)
This study aimed to describe the impact of using Virtual Reality (VR) in environmental education for school students. Environmental education is essential for enhancing students’ ecological understanding, awareness, and pro-environmental behaviours. However, today’s digital native generation is at risk of experiencing nature-deficit. VR is considered capable of bridging limited access to real nature through immersive and contextual virtual experiences. This research employed a Systematic Literature Review (SLR) method using the PRISMA protocol, analysing nine selected articles from Scopus and ScienceDirect databases. Findings indicated that VR use improves students’ understanding of ecological concepts, facilitates the internalisation of abstract material, nurtures connectedness to nature, and fosters empathy and pro-environmental attitudes. Integrating local cultural elements into VR learning also enhances students’ appreciation of indigenous wisdom and ecosystem conservation. Nevertheless, the study identified technical challenges in VR access and a lack of long-term research. This study is beneficial for teachers, schools, and educational psychologists in developing technology-based environmental learning to build students’ ecological identity and environmental citizenship in a holistic and sustainable manner.